Magneto-orbital helices as a route to coupling magnetism and ferroelectricity in multiferroic CaMn₇O₁₂ - Perks, N; Johnson, R; Martin, C; Chapon, L; Radaelli, P (Springer Nature, 2012)
Orbital physics drives a rich phenomenology in transition-metal oxides, providing the microscopic underpinning for effects such as Colossal Magnetoresistance. In particular, magnetic and lattice degrees of freedom are coupled through orbital ordering, and it has long been hoped that this coupling could be exploited to create high-temperature multiferroics with large values of the electrical polarization. Here we report an unprecedented magneto-orbital texture in multiferroic CaMn7O12, found to give rise to the largest magnetically induced ferroelectric polarization measured to date. X-ray diffraction characterization of the structural modulation in these ‘magneto-orbital helices’, and analysis of magnetic exchange shows that orbital order is crucial in stabilising a chiral magnetic structure, thus allowing for electric polarization. Additionally, the presence of a global structural rotation enables the coupling between this polarization and magnetic helicity required for multiferroicity. These novel principles open up the possibility of discovering new multiferroics with even larger polarization and higher transition temperatures.